Strengthening the Ecovillage Concept Through the KOMPAK Program Based on Organic Waste Processing into Compost Fertilizer in Segorogunung Village - Sorin, Aiyuhan; Nadifah, Zulfa; Azharie, Dhian; Hapsari, Pramudita; Rietmadanti, Rifa; Amelia, Putri; Sari, Novita; Wananditasari, Irene; Artsitania, Andini; Noviani, Rita (Society : Jurnal Pengabdian Masyarakat, 2026)
Segorogunung Village is one of the villages in Ngargoyoso District with considerable plantation potential. Plantation activities generate abundant organic waste; however, most residents still manage waste through open burning. This practice may cause negative environmental and health impacts, thus requiring more sustainable waste management alternatives. This community service program aimed to improve community understanding of organic waste management through the KOMPAK Program (Kompos Organik Masyarakat Produktif dan Berkelanjutan) as an effort to strengthen the ecovillage concept in Segorogunung Village. The activity was conducted on April 20, 2026, at the Segorogunung Village Hall involving local residents, Geography Education students of Universitas Sebelas Maret, the Segorogunung Village Government, and the Environmental Agency of Karanganyar Regency. The methods employed included observation, lectures, discussions, and compost-making demonstrations. Observation results indicated that plantation land use dominates the village economy and produces a significant amount of organic waste. Through socialization and practical composting activities, participants gained knowledge regarding the utilization of organic waste as useful compost fertilizer. The KOMPAK Program represents a community-based environmental management initiative that contributes not only to waste reduction but also to the sustainability of agricultural and plantation activities in Segorogunung Village.